CLASS EVALUATION: DEVELOPMENT OF HIGHER ORDER THINKING SKILLS TEST INSTRUMENTS IN DIGESTIVE SYSTEM LEARNING - Sumiati, Iis; Windayani, Neneng; Farida, Ida; Cahyanto, Tri (Prodi Pendidikan Biologi, FPMIPATI, Universitas PGRI Semarang, 2025)
In an era of ever-developing education, it is important to ensure that the evaluation tools used in the classroom can reflect students’ true abilities in understanding complex concepts. Measuring higher order thinking skills (HOTs) is an integral part of assessing student understanding. The aim of the research is to develop and validate a test instrument specifically designed to measure higher order thinking skills in digestive system learning at the secondary school level. The Higher Order Thinking Skills framework by Resnick, 1987 was used to develop the instrument. This research uses a Research and Development Design (R&D) approach by adapting the ADDIE model which consists of five stages, that is: Analysis, Design, Development, Implementation and Evaluation. The research sample consisted of 30 class IX students at Al-Qona'ah Middle School who were selected using a simple random sampling technique. The research results showed that there were eight out of ten valid questions with high reliability that were ready to be used to comprehensively measure students' HOTs abilities.